2011
DOI: 10.1111/j.1748-1716.2011.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischaemia/reperfusion injury: possible role of aquaporins

Abstract: Renal ischaemia/reperfusion (I/R) injury is a common problem that occurs when blood flow is interrupted to the kidney in case of kidney transplantation, aortic cross-clamping and shock with subsequent resuscitation. Renal I/R injury is a complex conditions which includes the onset of an inflammatory process, which is associated with impairment of concentrating ability of the kidney and impairment of solute transport. Characteristically, renal I/R injury is associated with marked reduction in the protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
(57 reference statements)
0
18
0
2
Order By: Relevance
“…We found that VDD-induced urinary concentrating defect. Ischemia/reperfusion is associated with a marked reduction in the renal protein expression of AQP1, AQP2, and AQP3 (Hussein et al 2012). However, the mechanism by which vitamin D downregulates AQP2 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that VDD-induced urinary concentrating defect. Ischemia/reperfusion is associated with a marked reduction in the renal protein expression of AQP1, AQP2, and AQP3 (Hussein et al 2012). However, the mechanism by which vitamin D downregulates AQP2 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying IR-induced AKI are not fully understood, but it has been suggested that the mechanisms are most likely multifactorial and interdependent, including endothelial and epithelial cell death, intratubular obstruction, changes in local microvascular blood flow, as well as immunological and inflammatory processes [28], [48], [49]. It is not excluded that LMWF may prevent kidney injury and promote kidney repair after IR by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Renal I/R injury results in down-regulation of aquaporins and sodium transporters [29], [33]. Aquaporins and sodium transporters are important for the renal reabsorptive capacity of water and sodium.…”
Section: Discussionmentioning
confidence: 99%